2023
DOI: 10.1007/s00412-023-00803-9
|View full text |Cite
|
Sign up to set email alerts
|

Casting histone variants during mammalian reproduction

Abstract: During mammalian reproduction, germ cell chromatin packaging is key to prepare parental genomes for fertilization and to initiate embryonic development. While chromatin modifications such as DNA methylation and histone post-translational modifications are well known to carry regulatory information, histone variants have received less attention in this context. Histone variants alter the stability, structure and function of nucleosomes and, as such, contribute to chromatin organization in germ cells. Here, we r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 178 publications
(258 reference statements)
0
4
0
Order By: Relevance
“…It has been established that H1–8 is necessary for bovine subjects during the preimplantation stage . More recently, a review concluded that H1–8 is activated during the germinal vesicle stage, effectively replacing core histone H1 until the oocyte reaches full maturity (MII) in mice . A study published in 2023 demonstrated a correlation between H1–8 expression and oocyte maturity in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that H1–8 is necessary for bovine subjects during the preimplantation stage . More recently, a review concluded that H1–8 is activated during the germinal vesicle stage, effectively replacing core histone H1 until the oocyte reaches full maturity (MII) in mice . A study published in 2023 demonstrated a correlation between H1–8 expression and oocyte maturity in humans.…”
Section: Discussionmentioning
confidence: 99%
“… 15 More recently, a review concluded that H1–8 is activated during the germinal vesicle stage, effectively replacing core histone H1 until the oocyte reaches full maturity (MII) in mice. 16 A study published in 2023 17 demonstrated a correlation between H1–8 expression and oocyte maturity in humans. Until now, its presence at the protein level has not yet been confirmed, but here we present for the first time convincing evidence of existence for H1–8 protein expression in human oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The H2A family, with 19 mammalian variants reported to date, is the most diverse histone family among the other core histones ( Table 1 ). The amino acid sequences of the 19 histone H2A variants vary greatly from one another but remain highly conserved during evolution, indicating that they all carried out indispensable functions [ 17 , 21 , 22 ]. In contrast to the other three classes of canonical histones, H2A proteins have both N– and C–terminal tails.…”
Section: The 19 Histone H2a Variantsmentioning
confidence: 99%
“…3.4. Short H2A (sH2A)-H2A.R Short H2A histone (sH2A) is a group of H2A variant which displayed a testis-restricted transcription pattern and are expressed exclusively during mammalian spermatogenesis [21]. sH2A is one of the most rapidly evolving group of histone variants and was originated from placental mammals.…”
Section: Macroh2a and Isoforms-novel Prognostic Factor And Diagnostic...mentioning
confidence: 99%